Ireland since the famine: a sketch of fifty years' economic and legislative changes - Bailey, William F. (Statistical and Social Inquiry Society of Ireland, 1906)
In addressing you this evening I propose to review, as shortly as the subject will admit, the economic and legislative changes that have taken place in Ireland during the last half-century?to take stock of our position as a commercial house takes periodical stock of its goods, an operation useful and instructive, because it helps to an understanding of the present, the first step towards further progress. That much has been done to improve the condition of the country and of its people during the last half century will be admitted by most persons, although many may differ as regards the means employed and the results achieved. My object in making this survey is not to prove that the economic and social condition of Ireland is as satisfactory as possible, that the existing order of things is all that can be desired, and that no change for the better is possible. The great principles of evolution and development are now too well recognised as governing all life?social, economic and political?to permit of such a standpoint being maintained. Society is based on continuous movement and change. Things cannot stay as they are.
Read Friday, November 21st, 1902
Keywords: Social change, Ireland, Post-famine; Economic progress, Ireland, Post-famine; Post-famine Ireland; 314.15